Occurrence and pathogenicity of indigenous entomopathogenic fungi isolates to fall armyworm (Spodoptera frugiperda J. E. Smith) in Western Amhara, Ethiopia - Mekonnen, Mequanint Andualem; Emirie, Gebremariam Asaye; Mitiku, Solomon Yilma; Hailemariam, Bogale Nigir; Mekonnen, Melkamu Birhanie; Mengistu, Anteneh Ademe (Cambridge Entomological Club, 2024)
The fall armyworm (FAW) (Spodoptera frugiperda J. E. Smith) is widely recognized as an invasive lepidopteran pest in Africa. Adoption of synthetic pesticides remains an option for emergency control of the FAW, but their large-scale use by small-scale farmers is costly and environmentally unsafe. Management options based on entomopathogenic fungi could minimize risks for health and the environment. In our study, the occurrence of entomopathogenic fungi in different habitats along with their pathogenicity to fall armyworm was examined. A total of 56 soil samples were collected from three locations. A standard isolation method, baited with the wax moth larvae (Galleria mellonella), was used for the isolation of entomopathogenic fungi from soil. Twelve entomopathogenic fungi were isolated from the total soil samples collected. It was observed that Metarhizium spp. was more frequent and widespread than Beauveria spp. and their occurrence was high in the forest habitat. Pathogenicity of indigenous entomopathogenic fungi isolates on fall armyworm larvae was tested by applying conidial suspension containing 1 × 108 spores/ml. All of the isolates tested were pathogenic to larvae of fall armyworm, with mortalities varying from 30 to 80% at 10 days posttreatment. Our results suggest that native entomopathogenic fungi could be integrated for the management of Spodoptera frugiperda larvae.